Accelerating N-Body Simulation of Self-Gravitating Systems with Limited First-Order Post-Newtonian Approximation (Communications in Computational Physics, 2018)
In this study, an N-body simulation code was developed for self-gravitatingsystems with a limited first-order post-Newtonian approximation. The code was appliedto a special case in which the system consists of one massive object and manylow-mass objects. Therefore, the behavior of stars around the massive black hole couldbe analyzed. A graphics processing unit (GPU) was used to accelerate the code execution,and it could be accelerated by several tens of times compared to a single-coreCPU for N ≃104 objects.